2022
DOI: 10.1126/scitranslmed.abg7859
|View full text |Cite
|
Sign up to set email alerts
|

GABABreceptor modulation of visual sensory processing in adults with and without autism spectrum disorder

Abstract: Differences in GABAergic function are critical to autistic visual sensory neurobiology and can be modulated by targeting GABA B .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 87 publications
5
30
0
Order By: Relevance
“…This show that there are likely associations of glutamatergic and GABAergic gene-expression to alterations in sensory processing but that differences may be too subtle between groups to show any differences. These associations, combined with the trend significant associations of aggregated genetic variance of the GABA gene-set are in line with previous work indicating that alterations of GABA are associated with altered sensory processing in autism [ 32 , 71 , 72 ]. It is also possible that we did not see significant associations with CT-difference scores between these groups due to lower number of participants on the moderate and severe groups ( n = 37, n = 18 respectively).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This show that there are likely associations of glutamatergic and GABAergic gene-expression to alterations in sensory processing but that differences may be too subtle between groups to show any differences. These associations, combined with the trend significant associations of aggregated genetic variance of the GABA gene-set are in line with previous work indicating that alterations of GABA are associated with altered sensory processing in autism [ 32 , 71 , 72 ]. It is also possible that we did not see significant associations with CT-difference scores between these groups due to lower number of participants on the moderate and severe groups ( n = 37, n = 18 respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Ultimately, E/I balance may be manipulated using glutamate- and/or GABA- influencing pharmacological treatments. One study already showed decreased glutamate and GABA concentrations after bumetanide treatment to be positively associated with autism symptom improvement [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in GAD1 levels may lead to a decrease in inhibitory GABA signaling, resulting in hippocampal excitatory/inhibitory imbalance, abnormal synaptic plasticity, and abnormal formation of the neural network, thereby interfering with hippocampal function [ 33 ]. Furthermore, the excitation of GABA receptors reversed repetitive and stereotyped behaviors in two ASD models [ 36 ], and the differences in GABAergic function underlie the sensory neurobiology of autism [ 37 ]. Accordingly, the increased ApoA-I-SphK levels in ASD model mice may be involved in the occurrence and development of the downregulation of GAD1 in the hippocampus, potentially reducing the production of GABA in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Participants provided written informed consent for an experimental medicine study comprising a series of experiments to investigate the role of GABA on ASD (13) approved by King's College Research Ethics Committee (RESCM-17/18-4081).…”
Section: Methodsmentioning
confidence: 99%
“…Given the evidence for higher neural reactivity (weaker suppression) to repetitive stimuli in children with ASD and infants at-risk of ASD ( 2, 56, 57 ) and reports of ASD-related alterations in the GABA system ( 10, 13, 15 ), we had two main predictions: (i) Repetition suppression reflected by oscillatory responses to standard tones would be atypical in ASD relative to TD; (ii) Repetition suppression would be differentially modulated by challenging the GABA system in ASD and TD. In contrast, we did not expect to find significant case-control differences in the event-related MMN signal in this adult cohort, nor any statistically significant modulation of ERPs in response to GABA B agonism.…”
Section: Introductionmentioning
confidence: 99%